Corticosteroidi per via Intravitreale per il Trattamento Dell'edema Maculare: Revisione e Valutazione Della Qualità Dell'evidenza. Issue 1 (2017) - Marchetti, Marco; Urbina, Luz Irene; Oradei, Marco; Ruggeri, Matteo; Navarra, Pierluigi
Intravitreal corticosteroids for the treatment of macular edema: review and assessment of quality of the evidence: Introduction: Treatment options for macular edema include intravitreal corticosteroids. Traditionally, an injectable suspension of triamcinolone acetonide (TA) had been employed off-label; in recent years, authorities have approved sustained-release drug delivery systems (DDSs) for corticosteroids. This review aims to compare the quality of the evidence on efficacy and safety of three different formulations of intravitreal corticosteroids: the dexamethasone (DEX) implant, the fluocinolone acetonide (FA) implant, and the preservative-free injectable suspensions of TA, in the management of two retinal pathologies: diabetic macular edema (DME) and macular edema secondary to retinal vein occlusion (RVO). Methods: A search of clinical trials on MEDLINE from 01/01/2000 to 12/16/2015 was performed. Studies were included in the analysis if they met the following criteria: i) related to at least one of the preparations of interest in patients with DME or macular edema secondary to RVO; ii) included a control group treated with placebo, observation, sham procedures or conventional treatments; and iii) included visual acuity, retinal thickness and/or safety parameters as outcomes. Results were summarized in a narrative manner. Results: Twenty-five publications from 19 RCTs were included. We observed increased attention of researchers towards TA compared to DEX and FA; however, studies for TA are less robust. Scientific publications related to DEX and FA implants are of higher quality, especially in terms of randomization and masking procedures. Discussion: Although trials on TA are numerous, evidence on DEX and FA implants is more robust. Since their introduction, these relatively new DDSs have been included in the main guidelines for the management of macular edema.